2017
DOI: 10.1093/icvts/ivx007
|View full text |Cite
|
Sign up to set email alerts
|

In patients undergoing lung resection is it safe to administer amiodarone either as prophylaxis or treatment of atrial fibrillation?

Abstract: A best evidence topic in thoracic surgery was written according to a structured protocol. The question addressed was whether the administration of amiodarone is safe in patients undergoing lung resection either for prophylaxis or treatment of de novo postoperative atrial fibrillation (POAF). A total of 30 papers were identified, of which 13 represented the best evidence to answer the clinical question. The authors, journal, date, study type, country of publication, patient demographics, relevant outcomes and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Diagnosis is based on high clinical suspicion, patient's history, radiographic and clinical findings. APT may occur even at any time during treatment or even after cessation of treatment [4] . Applying a cumulative dose of 400 mg/day for 2 months, long duration of therapy, advanced age, and pre-existing pulmonary disease increase the risk of pulmonary toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is based on high clinical suspicion, patient's history, radiographic and clinical findings. APT may occur even at any time during treatment or even after cessation of treatment [4] . Applying a cumulative dose of 400 mg/day for 2 months, long duration of therapy, advanced age, and pre-existing pulmonary disease increase the risk of pulmonary toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…I n i t i a l l y, amiodarone was considered unsafe in thoracic surgery after a small study in 1994 demonstrated an association between the use of amiodarone and acute respiratory distress syndrome (ARDS) after pneumonectomy (26). However, multiple studies have since demonstrated that low doses of amiodarone are safe and effective in patients with chronic lung disease (27,28). Magnesium has also been demonstrated to be effective in reducing the risk of AF.…”
Section: Recommendationmentioning
confidence: 99%
“…The difference may be that more recent studies have used lower doses. Patients in the 1994 trial patients received cumulative doses of over 2,000 mg IV whereas more recent trials have only used up to 1,050 mg IV, which has demonstrated to be safe and effective (27,28). As such, careful consideration of patient comorbidities should be considered prior to administering antiarrhythmic therapy and only low doses of IV amiodarone should be used in patients who have undergone major pulmonary resection.…”
Section: Post-operative Atrial Fibrillationmentioning
confidence: 99%
“…Considering the potentially negative impact of POAF on morbidity and mortality, possibly preventive effect of antiarrhythmic drugs has been investigated [7] [8] [9] [10] [11]. Between 2008 and 2011, Riber et al conducted the randomized control trial, PASCART, of which 242 patients undergoing surgery for lung cancer were randomized to receive either amiodarone or placebo, as prophylaxis for POAF.…”
Section: Introductionmentioning
confidence: 99%